Integration of intestinal microbiota and transcriptomic and metabolomic responses reveals the toxic responses of Litopenaeus vannamei to microcystin-LR - Duan, Yafei; Lu, Zijun; Zeng, Shimin; Dan, Xueming; Mo, Zequan; Zhang, Jiasong; Li, Yanwei (Ecotoxicology and environmental safety, 2021)
Microcystin-LR (MC-LR) is a hazardous hepatotoxin substance that threaten aquatic animals. Intestinal microbes can interact with and influence the health of their hosts. In this study, the shrimp Litopenaeus vannamei were exposed to 0.1 or 1 µg/L MC-LR for 72 h, and changes in intestinal microbial community and hepatopancreas transcriptome and metabolome were investigated. The results showed that both two doses of MC-LR increased intestinal microbial diversity and caused community composition variation by decreasing the abundances of putatively beneficial bacteria (Alloprevotella, Prevotella 1, Bacteroidales S24–7 group_norank and Lactobacillus). A large number of immune-related genes were differentially expressed in the hepatopancreas, including pattern recognition receptors and antimicrobial molecules; nutrient digestion and detoxification metabolism dysfunction were also induced. Furthermore, MC-LR altered hepatopancreas metabolic phenotypes, especially amino acid metabolism, the citric acid cycle, and linoleic acid and arachidonic acid metabolism. The changes in the intestinal bacteria were correlated with the immune factors and metabolic functions of their host. This study provides evidence for the toxicity of MC-LR on shrimp and identifies several biomarkers associated with the stress response. •MC-LR increased intestinal microbial diversity but decreased putative beneficial bacteria.•MC-LR influenced the detoxification and immune gene transcription.•MC-LR disrupts amino acids, linoleic acid and arachidonic acid metabolism.•Intestinal bacteria were correlated with the immune and metabolic molecular changes of their host.•A schematic model of the toxicological responses of MC-LR in shrimp was deduced.